Fertility‐sparing surgery for early‐stage cervical cancer: A case series study on the efficacy and feasibility of cervical conization followed by pelvic lymphadenectomy. Issue 6 (21st March 2022) - Yamamoto, Mayuko; Motohara, Takeshi; Iwagoi, Yutaka; Tayama, Shingo; Tashiro, Hironori; Kondoh, Eiji; Katabuchi, Hidetaka
Abstract: Objectives: To evaluate the oncologic and obstetric outcomes of cervical conization followed by pelvic lymphadenectomy, which is used as a fertility‐sparing procedure, in reproductive‐aged patients with early‐stage cervical cancer. Methods: We performed a retrospective study of patients with stage IA1–IB1 cervical cancer who underwent cervical conization followed by pelvic lymphadenectomy from 2011 to 2020 at Kumamoto University Hospital. Results: In total, eight patients underwent conization followed by pelvic lymphadenectomy. The median age of the patients was 33 (range: 28–36) years. Four (50.0%) patients were nulliparous. Seven (87.5%) patients were diagnosed with squamous cell carcinoma (87.5%) and one (12.5%) with adenocarcinoma. Five (62.5%), two (25.0%), and one (12.5%) presented with stage IA1, IA2, and IB1 disease, respectively. Five (62.5%) patients had lymphovascular space invasion (LVSI) based on the assessment of specimens obtained via conization. However, none had lymph node metastasis based on pelvic lymphadenectomy. Regarding long‐term oncologic outcomes, recurrence was not observed at a median follow‐up of 60 (range: 8–107) months. In addition, obstetric outcomes were consistently favorable in terms of achieving pregnancy, preterm delivery, and live birth. During the study period, two patients who actively attempted to conceive had four pregnancies, resulting in full‐term deliveries, and one was on her first trimester of pregnancy. Conclusion: Cervical conization combined with pelvic lymphadenectomy represents a feasible conservative management for histologically well‐selected patients with early‐stage cervical cancer. Furthermore, an optimal histopathological evaluation of conization specimens will contribute to decision‐making regarding the use of this fertility‐sparing procedure.